The Role of Free Zones in Economic Development in Oman (Field study on Salalah Free Zone) - Ahmed Hafid Braham Baamr, Adbelkader; Fatouh, Ibrahim (Finance and Business Economies Review, 2019)
The study aims to identify the role of free zones in achieving economic development in the Sultanate of Oman. The study society consists of employees working in the companies investing in Salalah Free Zone. The researcher used the descriptive analytical approach in this study. 100 questionnaires were distributed among the sample of the study and only 83 questionnaires were good for statistical analysis. The study concluded that there is a statistically significant for the role of free zones in the economic development, also found the existence of an statistical significance effect of the laws and exemptions from taxes and fees in economic development; as well as the existence of statistic ally influence significant of incentives for investment in economic development, and the existence of a statistically significant effect of infrastructure in economic development from the point of view of the employees working in companies invested in the free zone in Salalah. The Study recommends the establishment of an authority specialized in free zones. Also, it recommends increasing the budget of Salalah free zone to suit the size of the projects which are invested in Salalah free zones.